Pendampingan dan Pengenalan Teknologi Berbasis Internet kepada Anak Berkebutuhan Khusus di SLB C Budi Daya, Jakarta Timur - Fitria Ayuningtyas; Vinta Sevilla (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2020)
A normal child who is not lacking in anything physical or psychological is the dream of all parents. A hope regarding this matter is something that is natural for anyone. It's just that, in reality these hopes cannot be realized for some people. One of them is the presence of children with special needs in their lives. Even though every child has their own uniqueness and potential. One of the children with special needs is an autistic child. Autism is a very complex developmental disorder in a long life that includes disruption in aspects of social interaction, communication and behavior as well as emotional disturbances and sensory perceptions even in motoric aspects. Very severe disorders of some disorders experienced by children with autism that is a disorder in the ability to communicate. The ability to communicate nonverbally for children in general can be obtained naturally, without the need to be specifically and continuously taught for a long and long time. But the situation will be very different from autistic children. Autistic children need a design and learning strategy and approach to improve their nonverbal communication skills appropriately. Along with this, the development of Technology, Information and Communication (ICT) is inevitable. Most people think that the introduction and development of ICT knowledge is only for normal children. Through community service, the PKM team wants to share related developments in Technology, Information and Communication to children with special needs by using assistive devices and games specifically for children with special needs, especially children with autism. The implementation was carried out at SLB C Budi Daya, Cijantung, East Jakarta on 14 and 17 September 2018 ago.